Degradação térmica e catalítica dos polímeros poli (acrilonitrila-co-butadieno-co-estireno) (ABS) e poliestireno de alto impacto (HIPS) oriundos de resíduos eletroeletrônicos - Miranda, Débora Micheline Vaz de (2016)
The high consumption level and wide diversity of electrical and electronic equipment available nowadays caused the signi cant increase of obsolete materials and waste, which can be harmful to the environment and health if discarded incorrectly. As a consequence, it is necessary to develop e ective recycling techniques for the disposal of these wastes and to promote the return of the discarded materials to the manufacturing process. As acrylonitrile-butadiene-styrene (ABS) and highimpact polystyrene (HIPS) are two of the most often used plastics for electronic equipment manufacture, studies were carried out in order to assess the thermal and catalytic degradation of virgin and post-consumer polymer materials used for computer carcasses production. Studies were also performed for the co-pyrolysis of post-consumer carcasses with orange peel, used to simulate the presence and evaluate the in uence of organic matter, rich in oxygenates and water, on the process performance. The zeolites H-USY and H-ZSM5 were employed in both cases as catalysts. The results showed that it is possible to obtain large amounts of liquids (up to 90%), rich in aromatic compounds, constituted by around 60% of styrene monomer. The catalyst increased the amount of the gas fraction and changed the nature of the compounds, considerably reducing the amount of produced styrene. Meanwhile, the co-pyrolysis produced a two-phase product with large quantities of water (about 40%), although the percentage of styrene in the oil fraction was still in the range of 50-60%.